2008
DOI: 10.1080/02673030802425602
|View full text |Cite
|
Sign up to set email alerts
|

Visualising Household Energy Use in the Interest of Developing Sustainable Energy Systems

Abstract: Energy is an important social resource on which we depend in our everyday lives; however, energy-related emissions constitute a major environmental burden, so in Sweden a major political goal is to reduce total energy consumption and to use energy more efficiently. To achieve this, users need to transform their behaviour and start reflecting on their energy use. This paper discusses three different methods for visualizing energy use, namely information tools, keeping time diaries, and using the "Power-Are Cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…How energy is produced and distributed is not relevant from this point of view; the important thing is fulfilling those needs. (However, it might be relevant for the environmentally engaged person who emphasizes environmentally friendly energy production) [22][23]. The overall goal must in the end be to introduce ecologically sustainable solutions and then meet the challenge of integrating these solutions in such a way that they provide and sustain what people consider to be normal services.…”
Section: Influence Energy Consumption -Information and Feedbackmentioning
confidence: 99%
“…How energy is produced and distributed is not relevant from this point of view; the important thing is fulfilling those needs. (However, it might be relevant for the environmentally engaged person who emphasizes environmentally friendly energy production) [22][23]. The overall goal must in the end be to introduce ecologically sustainable solutions and then meet the challenge of integrating these solutions in such a way that they provide and sustain what people consider to be normal services.…”
Section: Influence Energy Consumption -Information and Feedbackmentioning
confidence: 99%
“…In a study on the use of an electricity monitor (PowerCost) by Mountain (2006), one third of the participants indicated they would not use the monitor any more after the pilot. Lofstrom and Palm (2008) addressed the use of the Power-Aware Cord, which can visualize the electricity use of a single socket. They tested it for two months with six households and found that whereas in the beginning people were enlightened by the energy use of an appliance, after some time the Power-Aware Cord 'just' became a decorative element, likened by all participants to Christmas lights.…”
mentioning
confidence: 99%
“…The greatest opportunities as mentioned by many articles are, Resource and waste optimisation (Bilal et al, 2015;Oyedele, 2016;Oyedele et al, 2013;Lu et al, 2015Lu et al, , 2016, Generative designs and clash detection and resolution (Nima, 2014;Wang and Leite, 2013), performance prediction (Abaza et al, 2004;Kobayashi et al, 2010), visual analytics (Goodwin and Dykes, 2012;Löfström and Palm, 2008), social networking services/analytics (Demirkesen and Ozorhon, 2017;Wolf et al, 2009), personalised services (Liu et al, 2012;Singh et al, 2010), facility management (Isikdag et al, 2013;Liu et al, 2012;Rueppel and Stuebbe, 2008;Taneja et al, 2012), Energy management and analytics (Hong et al, 2012;Linda et al, 2012;Sanyal and New, 2013), big data integration with BIM (Volk et al, 2014), big data integration with IOT and cloud computing (Elghamrawy and Boukamp, 2010), big data for augmented reality (AR) (Williams et al, 2015), use of big data for smart buildings and smart city/urban infrastructure (Khan and Hornbaek, 2011;Liu et al, 2014). Further, Mishra et al (2017) and Janssen et al (2017) purport that exploitation of BDA can lead to gain competitive advantage at any level.…”
Section: Data Synthesismentioning
confidence: 99%